Analisis Kinerja Fasilitas Operasi Perlintasan Sebidang (Studi Pada Resort 4.6 Smt) - Puspitasari, Mariana Diah (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2021)
PT Kereta Api Indonesia (KAI) during 2019 and 2018 calculated that there had been 655 accidents at level rail crossings. Accidents often occur in high traffic areas such as the Telecommunication Signal Resort 4.6 SMT. So the researchers conducted research in order to find out the performance of the railway operating facilities under the auspices of the Telecommunication Signal Resort 4.6 SMT as well as public perceptions of its performance. Researchers used a sound level meter to measure the loudness level of the level rail crossings siren sound at the research location. Furthermore, it is compared with the standards stipulated in the Minister of Transportation Regulation Number 44 of 2018. Then tested using Anova to find out whether the population mean will be of the same value using data from each population. Furthermore, an unstructured interview was conducted to hear the perceptions of road users on the performance of the operational facilities at level rail crossings which became the research object. The results showed that the five level rail crossings which were the object of the study had the loudness level of the siren sound below the set standard. In contrast, flat cross lights perform well. Meanwhile, the public perception of the operational facilities at level rail crossings is that they are functioning well. Keywords: level rail crossing, operating facility, railway